Relationships between xylem anatomy, root hydraulic conductivity, leaf/root ratio and transpiration in citrus trees on different rootstocks - Rodriguez-Gamir, Juan; Intrigliolo, Diego S.; Primo-Millo, Eduardo; Forner-Giner, María A. (2017)
The aim of the study was to determine the extent in which leaf and whole plant transpiration (Tp) were influenced by root hydraulic conductance (K(r)), leaf to root ratio and leaf mass. Also, the relationships between the anatomic characteristics of roots and K(r) were investigated. To this end, 9-month-old seedlings of the citrus rootstocks Cleopatra mandarin (CM), Poncirus trifoliata (PT), and their hybrids Forner-Alcaide no 5 (FA-5) and Forner-Alcaide no 13 (FA-13) and 15-month-old trees of Valencia orange budded on these four rootstocks were tested. The hybrid FA-13 and PT had higher values of K(r) and leaf transpiration rates (E) than FA-5 and CM. There was a positive curvilinear correlation between E and K(r). Furthermore, E levels in the different types of plants decreased with increased leaf/root (L/R) ratios. Pruning of the roots and defoliation confirmed that transpiration rates were strongly influenced by the L/R ratio. However, variations in E because of differences in L/R ratios were less pronounced in trees budded on FA-13 and PT than on the other two rootstocks. In addition, there was a positive correlation between Tp and leaf biomass, although differences between rootstocks may be attributed to differences in K(r). The average lumen diameter of xylem vessels was greater in rootstocks with high K(r). Size of epidermal and hypodermal cells of fibrous roots may also restrict K(r).